Hubungan antara Kualitas Tidur dan Depresi pada Komunitas Lansia Wanita di Dahlia Senja Limo Depok - Fildzah Alifah Maulani; Eko Prabowo; Rabia Rabia (Fakultas Ilmu Kesehatan, 2023)
An advanced process of life where the emergence of a state of organ function that decreases anatomically, physiologically and psychologically is a condition that often occurs among the elderly. An individual's sense of satisfaction with his sleep condition is another word for sleep quality. Depression is a common mental disorder. Objective: To understand whether there is a relationship between sleep quality and depression levels in the Dahlia Senja elderly community. Design: Using a cross-sectional method based on the results of examining sleep quality using the Pittsburgh Sleep Quality Index (PSQI) instrument and examining the level of depression using the Geriatric Depression Scale (GDS) instrument. The sample in this study was the elderly in the Dahlia Senja Senja Limo Depok Elderly Community with a total of 40 samples. By using the Chi-Square test data analysis. Results: It was reported that around 90% of the elderly had poor sleep quality and 55% of the elderly were in normal condition. The value in this study was 0.368 > 0.05 which indicated that there was no significant relationship between sleep quality and depression in the Dahlia Senja Senja Limo Depok Elderly Community